Analysis on the Incidence and Economic Burden of Patients with Lung Cancer - Guo TIAN; Li BIAN; Xiaoli XU; Shumei LI (Chinese Journal of Lung Cancer, 2022)
Background and objective The previous study has indicated that lung cancer has a high incidence and mortality in China, and has caused a large economic burden. The purpose of this study was to analyze the incidence and economic burden of lung cancer by analyzing the information on the home page of discharge history of lung cancer patients in Hebei Tumor Hospital, and to provide scientific basis for the prevention and treatment of lung cancer. Methods The information of all of the discharges, new cases, surgical patients, age, gender, length of stay and hospitalization cost of lung cancer patients in Hebei Tumor Hospital from January 2012 to December 2019 were retrieved based on the medical record management system, and the incidence trend, gender and age distribution as well as the economic burden of the disease were statistically described. Results The number of new cases of lung cancer increased year by year, from 2,235 cases in 2012 to 5,012 cases in 2019. The number of males always outnumbered females, but the gender ratio decreased year by year, from 2.25 in 2012 to 1.56 in 2019. Among new cases of lung cancer, the proportion of surgical treatment increased year by year, from 28.14% in 2012 to 44.83% in 2019. Except for 2012, the proportion of surgical operations in female patients was higher than that in male patients from 2013 to 2019. The proportion of surgical operations in male and female patients was 23.52% and 28.07% in 2013, and 36.14% and 58.37% in 2019, respectively. The median age at the onset of lung cancer has increased year by year, from 61 years old in 2012 to 63 years old in 2019. The median age of onset in all lung cancer patients was higher in males than in females. The number of new lung cancer patients and surgical patients both showed an increasing trend with the increase of age, and both reached the maximum value in the age group of 60-69 years old. With the increase of age, the number of patients gradually decreased. The median length of hospital stay for all discharged lung cancer patients or surgical patients decreased year by year, from 10 d and 19 d in 2012 to 8 d and 17 d in 2019, respectively, while the median hospitalization cost increased year by year. It increased from 10,611.46 yuan and 38,750.13 yuan in 2012 to 17,187.15 yuan and 84,030.16 yuan in 2019, respectively. Conclusion Lung cancer is still one of the main cancers endangering the health of Chinese residents. The incidence of lung cancer is increasing year by year, and the distribution of gender and age has certain characteristics. In order to reduce the number of cases and the economic burden, effective prevention and control measures should be formulated and medical reform should be strengthened.